Stigma for common mental disorders in racial minorities and majorities a systematic review and meta-analysis - Ozlem Eylem; Leonore de Wit; Annemieke van Straten; Lena Steubl; Zaneta Melissourgaki; Gözde Topgüloğlu Danışman; Ralph de Vries; Ad J. F. M. Kerkhof; Kamaldeep Bhui; Pim Cuijpers (BMC, 2020)
Abstract Background There is a strong stigma attached to mental disorders preventing those affected from getting psychological help. The consequences of stigma are worse for racial and/or ethnic minorities compared to racial and/or ethnic majorities since the former often experience other social adversities such as poverty and discrimination within policies and institutions. This is the first systematic review and meta-analysis summarizing the evidence on the impact of differences in mental illness stigma between racial minorities and majorities. Methods This systematic review and meta-analysis included cross-sectional studies comparing mental illness stigma between racial minorities and majorities. Systematic searches were conducted in the bibliographic databases of PubMed, PsycINFO and EMBASE until 20th December 2018. Outcomes were extracted from published reports, and meta-analyses, and meta-regression analyses were conducted in CMA software. Results After screening 2787 abstracts, 29 studies with 193,418 participants (N = 35,836 in racial minorities) were eligible for analyses. Racial minorities showed more stigma than racial majorities (g = 0.20 (95% CI: 0.12 ~ 0.27) for common mental disorders. Sensitivity analyses showed robustness of these results. Multivariate meta-regression analyses pointed to the possible moderating role of the number of studies with high risk of bias on the effect size. Racial minorities have more stigma for common mental disorders when compared with majorities. Limitations included moderate to high risk of bias, high heterogeneity, few studies in most comparisons, and the use of non-standardized outcome measures. Conclusions Mental illness stigma is higher among ethnic minorities than majorities. An important clinical implication of these findings would be to tailor anti-stigma strategies related with mental illnesses according to specific racial and/or ethnic backgrounds with the intention to improve mental health outreach.